Emergentism and complexity in Michael Polanyi’s thought - Passos Videira, Antonio Augusto; Muniz, Leandro Timotheo (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Submit an Article 1. Start 2. Upload Submission 3. Enter Metadata <li class="ui-tabs-tab ui-corner-top ui-state-default ui-tab ui-state-disabled" tabindex="-1" role="tab" aria-controls="ui-id-8" aria-labelledby="ui-id-7" aria-selected="false" aria-expanded="false" aria-disabled="true">4. Confirmation <li class="ui-tabs-tab ui-corner-top ui-state-default ui-tab ui-state-disabled" tabindex="-1" role="tab" aria-controls="ui-id-10" aria-labelledby="ui-id-9" aria-selected="false" aria-expanded="false" aria-disabled="true">5. Next Steps Prefix <input id="prefix-6276752626527" class="field text" maxlength="32" name="prefix[en_US]" type="text" value=""> Examples: A, The Title* <input id="title-627675262c277" class="field text required" maxlength="255" name="title[en_US]" required="1" type="text" value="" aria-required="true"> Subtitle <input id="subtitle-627675262c354" class="field text" name="subtitle[en_US]" type="text" value=""> Abstract* Starting from a relatively brief --but hopefully understandable-- description of Michael Polanyi’s ideas about emergentism and complexity, we will present a perspective of scientific knowledge under the aegis of two of his most relevant maxims: i) we know more than we can talk about, ii) in general, we employ more ideas than we define concepts. We will propose a conception of science from his views on the inexact, tacit knowledge, the self-regulation of science, the network, and the society of explorers in order to show that complexity and emergentism (almost always synonymous with novelty) are guiding threads, rarely visible, that organize such a conception. Complexity and emergentism are theses that express some of the most relevant features of Polanyian thought, since they help to understand the relations between scientific knowledge and the way the society of explorers carries out its actions based on an intertwining between knowledge network and tradition.